Ideal Cardiovascular Health Metrics Modify the Association Between Exposure to Chinese Famine in Fetal and Cardiovascular Disease: A Prospective Cohort Study - Ding, Xiong; Li, Jinfeng; Wu, Ying; Yang, Peng; Zhao, Dandan; Yuan, Xiaojie; Chen, Shuohua; Luo, Xiaoyan; Li, Yun; Wu, Shouling (Frontiers in Cardiovascular Medicine, 2021)
Background: No study had explored the modification effect of ideal cardiovascular health metrics (ICVHMs) on the association between famine exposure and risks of cardiovascular disease (CVD) so far. We aim to examine the effect of ICVHMs on the association between exposure to famine early in life and the risk of CVD in adulthood. Methods: A total of 61,527 participants free of CVD were included in this study from the Kailuan cohort. All participants were divided into three groups, included nonexposed, fetal exposed, and childhood exposed groups. Cox regression was used to estimate the effect of famine exposure and ICVHMs on CVD risk. Results: After a median of 13.0 (12.7–13.2) years follow-up, 4,814 incident CVD cases were identified. Compared with nonexposed participants, the CVD risk increased in participants with fetal famine exposure (HR: 1.21; 95% CI: 1.07-1.37), but not in childhood famine exposed participants. After stratifying by the number of ICVHMs, the increased CVD risk associated with fetal famine exposure was only observed in participants with less ICVHMs (≤2) (HR: 1.30; 95% CI: 1.11-1.52, P for interaction=0.008) but disappeared in those with three or more ICVHMs. The modified effect of ICVHMs was sex specific (P for sex interaction=0.031). Conclusions Exposing to famine in the fetal period could increase the risk of CVD in late life; however, ICVHMs might modify the effect of famine exposure on CVD risk, especially in men.